Experimental study of helical milling on CFRP (carbon fibre reinforced polymer) for the hole making process - Rahim, E. A.; Mohid, Z.; Mat, K. C.; Jamil, M. F. M.; Koyasu, R.; Sasahara, H. (Trans Tech Publications, 2012)
Generate borehole by helical milling process may be used effectively since accurate location of the hole may be secured by means of the feed screw graduations. Fiber delamination which is the main defect occurred during hole making process on carbon fiber reinforced polymer (CFRP) were investigate throughout an experimental study. Effects of thrust force (Fz), delamination factor (Fd) and surface roughness are evaluated. Objective of the experiment are to find best cutting parameter and tool design suitable to performed helical milling operation on CFRP. Two types of end mill with 4 flutes were used and results are evaluated. It was found that tool design 2-1 has higher performance on CFRP.